Distance learning and face-to-face learning in a pathophysiology problem-based learning course during a pandemic - Chen, Fang-Hsu; Wu, Po-Jen; Chi, Chih-Hsien (Frontiers in Education, 2023)
During COVID-19, the education method has adjusted the conventional in-person classes to distance learning in the past two years. Most classes were lectures that could go well if the participants were familiar with the online operation and had a stable network environment. Nevertheless, problembased learning (PBL) classes rely on many discussions and still have communication and group development limitations. Here, we surveyed the learning effects of face-to-face (FF) and distance learning (DL) in the medical PBL course for two classes. Tutors and students were requested to give grades for five key areas (participation, communication, preparation, critical thinking, and group skills).Compared with FF and DL methods, our research clarified that student learning effects would reduce participation, communication, and group skills by questionnaire survey. The tutors' perspective regarded participation and communication ability as reduced at distance learning. Nevertheless, one of the two classes showed no difference in group skills.Our research provides an experience for the PBL class focusing on discussion and communication.In the post-pandemic era, whether face-to-face or distance learning should be appropriately adjusted to let students conduct effective communication in time.